The Supply Chain Disruption Framework Post COVID-19: A System Dynamics Model. Issue 4 (November 2020) - Sinha, Deepankar; Bagodi, Virupaxi; Dey, Debasri
The COVID pandemic seems to have raised the question, 'whether existing supply chain (SC) disruption philosophies and strategies continue to remain valid?'. This article assesses the differences in the business scenarios pre-and post-COVID. The authors capture the mathematical and operational relationships amongst the relevant factors and propose a System Dynamics (SD) model to carry out the simulations. The approach considers the impact of the force majeure condition, that is, COVID period on individuals' income, prices and demand of goods, cost of input and supply of finished goods. The results show that earnings may increase demand but, disruption in supplies of raw materials and finished products nullify the effect. On the other hand, even if flow returns to normal, reduced income affects normal goods businesses. JEL Codes: R41